A Domain Decomposition Based Spectral Collocation Method for Lane-Emden Equations (Communications in Computational Physics, 2018)
A domain decomposition based spectral collocation method is proposedfor numerically solving Lane-Emden equations, which are frequently encountered inmathematical physics and astrophysics. Compared with the existing methods, thismethod requires less computational cost and is particularly suitable for long-term computation.The related error estimates are also established, indicating the spectral accuracyof the method. The numerical performance and efficiency of the method areillustrated by several numerical experiments.